Operational evaluation of a radial flow thresher prototipe for sorghum (Sorghum bicolor) (L.) Moench) - Mantovani, Evandro Chartuni; Sobrinho, Antônio Timóteo; Martyn, Peter John; Bertaux, Serge (Pesquisa Agropecuaria Brasileira, 1995)
A prototype of a radial flow thresher driven by a gasoline engine, was built at the Universidade Federal de Viçosa, and tested at the National Maize and Sorghum Research Center of EMBRAPA. The machine operated at periplieral speeds of 7, 11, 15, and 18 m/s, threshing sorghum with 12, 16, 20 and 24%, of moisture content (w.b.). A factorial design with four randornized blocks was used in the statistical analysis of the data. The combination leading to the best overall performance associated the 18 m/s peripheral speed with the 20% moisture (w.b.) grain sorghum.
Keywords: sorghum threslier; small threslier; mechanical damage thresher; performance